Shockflation in the EU: Sectoral shocks, cost-push inflation and structural asymmetries in core and periphery countries - Vicente Ferreira; Jo\~ao Ferreira; Dario Guarascio; Francesco Zezza (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
The return of inflation in Western economies has fueled the debate on its main drivers, bringing sector-specific shocks and supply chain bottlenecks to the forefront. Building on the seminal approach of Weber et al. (2024), this paper develops a method to assess the degree of exposure to these shocks in EU countries. Using inter-country input-output data stemming from the FIGARO database, we identify systemically significant sectors in four regions within the EU: Core, Southern Periphery, Eastern Periphery, and financial hubs. We also analyze exposure to foreign shocks. Two main conclusions can be drawn: on the one hand, periphery countries are more exposed to shocks originating in the EU core than the other way around; on the other hand, all EU regions are considerably exposed to price shocks originating from non-EU countries (namely, Russia and China). The strategic dependencies of the block pose challenges for price stability and require targeted policies.
Keywords: C67; E31; E61; 330; Inflation; Supply chain shocks; Input-Output; Core-periphery